Evaluation of Electrostatic Separation of Microplastics From Mineral-Rich Environmental Samples - Enders, Kristina; Tagg, Alexander S.; Labrenz, Matthias (Frontiers in Environmental Science, 2020)
Reliable, easy, cost-effective and reproducible ways of extracting microplastics (MP) from environmental samples remains an important requirement for MP research. In this context, electrostatic separation is a new proposition, especially for extracting MP from mineral-rich samples and large sample volumes. However, there is little research evaluating the reliability of the technique. This study has evaluated the effectiveness of the Korona-Walzen-Scheider (KWS) system; a small-scale version of larger machines designed to sort recycling materials. Recovery rates of a variety of sizes of MP, spiked in beach sediments, were found to be highly dependent on the MP size. MP ≥ 2 mm achieved 99 - 100% recovery (with the exception of fibres: 80%), MP of 63 – 450 µm achieved 60 – 95% recovery and MP of 20 µm achieved 45% recovery. For particle-based analysis, additional density separation is still inevitable for the analysis of small MP after KWS separation and further reduces the overall recovery rates. Mass reduction rates of beach and commercial reference sand greatly differed, 93% and 17%, respectively. Mineral analysis using SEM-EDX suggested that lower reduction rates found in commercial sand was due to high presence of small (<50 µm) calcite particles. Tests based on environmental soil samples revealed comparatively low mass reduction rates ( 1%), suggesting that KWS treatment was inefficient for soils due to high levels of fine particulates. Sieving to remove fine particles improved mass reduction, though only to 15%. To specifically test for influence of fine particulates, recovery rates were determined for sand samples spiked with a defined amount of silicate dust, resulting in a reduction of certain MP recovery rates, especially medium-sized (450 µm) MP. Conclusively, several key influential parameters were identified, such as mineral composition and grain size, that can negatively effect sediment mass reduction as well as MP recovery rates. Given the variability in recovery rates, the use of internal standards is recommended when using the KWS, particularly for smaller MP (<500 µm). For large-volume (beach) sand samples, where interest is mainly in MP > 450 µm, electrostatic separation is a reliable and fast approach for MP extraction from the environment.